The Effect of Digital Content Marketing, Price Fairness, on Repurchase Intention mediated by Brand Image at Super Air Jet Aviation Company - Fajar Tri Irawan; Ramadhan Alamsyah; Irwan Chairudin; Imam Ozali (Green Publisher, 2025)
Indonesia as an archipelago with thousands of islands and a population of more than 255 million people has a vital need for transportation, especially air. Air transportation is considered superior in terms of speed and relatively better safety. The growth of the air transportation sector is considered to reflect economic growth. Repurchase intention is important for airline companies as it has a direct impact on their business continuity and success. This study aims to investigate the factors that influence the repurchase intention of Super Air Jet customers, considering the role of brand image as a mediator. This study utilizes quantitative research methods with purposive sampling. With respondents over 20 years old and have used SAJ Airline. Respondents collected were 160 respondents. The data was analyzed using SEM-PLS 3.0 software with outer model and inner model tests. The findings found that Digital Content Marketing has no significant effect on Repurchase Intention when mediated by Brand Image. In contrast, Price Fairness and Brand Image play a siqnificant role in influencing repurchase intentions as they create positive perceptions and build strong relationships between customers and companies.